Perbedaan Tingkat Depresi Saat Menjalani Pembinaan Intra Mural dengan Saat Menjalani Pembimbingan pada Warga Binaan Pemasyarakatan - Elga Putri Indanarta; Mohammad Fanani; Lilik Wijayanti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Correctional coached people, both in intra mural and in parole coaching are vulnerable to get depression. Depression is a syndrom of depressed mood with sympthoms and signs of pathologic sadness and suffering components. This study aimed to proof the difference of depression levels between inmates who are in intra mural coaching and correctional clients who are in parole coaching that inmates are higher than correctional clients. Methods: This analytic study was observational with cross-sectional approach. 20 inmates who are in intra mural coaching at Class I Detention Center Surakarta (group 1) and 10 ex-inmates who had intra mural coached in Class I Detention Center Surakarta that now under parole coaching as correctional clients by Class II Correctional Center Surakarta (group 2) were taken as samples by total sampling from available population. The primary data were collected by questionnaire of Beck Depression Inventory that answered by the respondens after received some instructions. The data were analyzed using t test on Statistical Package for the Social Sciences (SPSS) version 16.0 for Windows. Results: Group 1 had depression score (meandeviation standart) 23.857.13 and group 2 had 13.107.25. t test showed that depression levels of those groups were significantly different with p=0.002 (p<0.05). Conclusion: There is a statistically significant difference between depression level on inmates who are in intra mural coaching and on clients who are in parole coaching under the supervision of correctional system. Inmates who are in intra mural coaching had higher level of depression than ex-inmates who are in parole coaching as correctional clients. Keywords: depression, inmates, clients, correctional coached people